Profiles of Perfectionistic Automatic Thoughts and differences in the vividness of mental images (European Journal of Child Development, Education and Psychopathology, 2020)
Perfectionistic Automatic Thoughts (PAT) are a personality trait of a maladaptive character. These are known as those thoughts that tend to establish concerns about always maintaining a perfect situation, which triggers high demands and excessive efforts. Hence, its link with anxiety and stress. However, scientific research opts for interventions through mental images that increase well-being in people with high stress, as well as other psychopathological disorders, which raises questions about whether this type of intervention could be adequate to reduce PAT. The objective of this study was to observe if there are different profiles with PAT in university students, as well as if there are statistically significant, differences with the degree of vividness of mental images in a sample of 419 Spanish students (Mage = 21.7; SD = 5.13). For this, the Perfectionism Cognitions Inventory was administered as well as the Vividness of Visual Imagery Questionnaire-Revised Version-12. The results confirm profiles of low, moderate and high intensity. In addition, statistically significant differences were observed between groups with low and high PAT, as well as low and moderate PAT in terms of spatial images in motion and the creative ability of images. The findings of this study reveal and advance in the knowledge of PATs.